Analisis Penggunaan Aplikasi Gofood Dalam Pemasaran Umkm Kuliner Di Bekasi - Wachyuni, Suci Sandi; Hardiningsih, Desy (Politeknik Sahid, 2022)
Marketing is one of the activities determining the success of achieving company goals. Digital marketing is emerging as an innovative medium for entrepreneurs. E-commerce is the buying, selling, and marketing of goods and services through electronic systems. GoFood provides opportunities for business actors who want to compete digitally. This study aimed to analyze the effect of using the GoFood application on culinary UMKM in Bekasi. This study uses qualitative and quantitative research methods using primary and secondary data. The indicators used in the GoFood application use variables are ease, attitude, and behavior control. The needle used in the GoFood application's influence variable is usability. This study uses data collection techniques of observation, interviews, and questionnaires. Data sources were taken from 5 respondents through a purposive sampling technique with the condition that culinary UMKM has used GoFood for over a year. With the results, the average value (mean) of using the GoFood application is 4.12, and the average value (standard) of the effect of the GoFood application is 4.2. Culinary UMKM revenue increased by 26.6% after using GoFood from the previous year. So, it can be concluded that using the GoFood application affects the income of culinary UMKM in Bekasi.